2018
DOI: 10.5551/jat.cr002
|View full text |Cite
|
Sign up to set email alerts
|

Guidance for Pediatric Familial Hypercholesterolemia 2017

Abstract: This paper describes consensus statement by Joint Working Group by Japan Pediatric Society and Japan Atherosclerosis Society for Making Guidance of Pediatric Familial Hypercholesterolemia (FH) in order to improve prognosis of FH.FH is a common genetic disease caused by mutations in genes related to low density lipoprotein (LDL) receptor pathway. Because patients with FH have high LDL cholesterol (LDL-C) levels from the birth, atherosclerosis begins and develops during childhood which determines the prognosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 42 publications
2
74
0
Order By: Relevance
“…This is not surprising given the very different care-pathways, policies and diagnostic strategies used in the different countries and to a large extent reflects the maturity of the FH child diagnostic work across Europe, with the paediatrician in Greece having started clinical practice more than 20 years ago, routinely testing cholesterol concentrations in all children before the age of 3. In the other countries where diagnosis is performed mainly through family cascade screening (after known diagnosis in parent) the median age at diagnosis is between 8 and 11 years, which is in line with paediatric FH guidelines that recommend the testing and identification of children at risk of FH by the age of 8-10 years [9][10][11][12][13][14]. The lipid profile at diagnosis is relatively uniform across countries, with mean LDL-C 5.70 ( ± 1.44) mmol/l, although with Greece having the highest and Austria the lowest values, due most probably to patient selection criteria.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…This is not surprising given the very different care-pathways, policies and diagnostic strategies used in the different countries and to a large extent reflects the maturity of the FH child diagnostic work across Europe, with the paediatrician in Greece having started clinical practice more than 20 years ago, routinely testing cholesterol concentrations in all children before the age of 3. In the other countries where diagnosis is performed mainly through family cascade screening (after known diagnosis in parent) the median age at diagnosis is between 8 and 11 years, which is in line with paediatric FH guidelines that recommend the testing and identification of children at risk of FH by the age of 8-10 years [9][10][11][12][13][14]. The lipid profile at diagnosis is relatively uniform across countries, with mean LDL-C 5.70 ( ± 1.44) mmol/l, although with Greece having the highest and Austria the lowest values, due most probably to patient selection criteria.…”
Section: Discussionsupporting
confidence: 55%
“…However, there are a sizable proportion, which differs between countries, of children aged over 10 years old who have LDL-C above the EAS guideline recommendation of 3.5 mmol/l, who are not being treated with statin or other lipid lowering medication. Since ultrasound studies have demonstrated significant carotid intima-media thickening in non-treated FH children of this age compared to their non-FH siblings [34][35][36], and clinical trials have shown that statin treatment can reverse this [19,37,38], considering initiation of statin therapy by the age of 8-10 years is a recommendation in most recent guidelines [9][10][11][12][13][14]. While, for ethical and practical reasons, there are no long term randomised-placebo controlled trials to examine the benefit of statin initiation at this age and LDL-C level, observational studies over at least 20 years support the reduction of CVD risk associated with this approach [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, atherosclerotic cardiovascular disease (ASCVD) that usually starts in middle age or letter was also reported to progresses rapidly at an age of around 10 years in patients with FH. Hence, guidelines for Europe and America highlights that early diagnosis of FH and statin treatment from childhood are necessary for preventing the early-onset ASCVD [4,5].…”
Section: Introductionmentioning
confidence: 99%